188 - SYSTEMATIZING SCIENTIFIC BIBLIOGRAPHY OF WHAT'S SEXUALITY DURING THE PREGNANCY: A REVIEW (Fiep Bulletin - online, 2011)
Pregnancy is a biological process that impacts on the social, economic, emotional, psychological and sexual man and woman. In addition, pregnancy can have different meanings for each partner and the couple. Thus, this study is important because health professionals can be exploited in order to know the national and international reality and the way of how this object of study is being published in order to give the customer a holistic care, especially in regard to prenatal care, aiming at promoting health in the family. This is a literature, whose aim is to characterize the scientific literature on pregnancy and sexuality published in the BVS / BIREME, national and international level in cutting time from 2005 to 2009 in English, Portuguese, Spanish and in text full or summary, as the database, year of publication, study type, method, form of publication, category and country of publication. 102 studies were found, of this total, most of the papers surveyed were used in the study, descriptive, and qualitative and published in summary form. The work had great publication in 2006, as the language in which the works were published; more than 70.0% of the articles were in English. Countries like USA, Brazil and Thailand relied on more than 50.0% of publications. The categories addressed most of the work was about adolescence, sex education, existing illnesses during or after pregnancy and ethical and moral dilemmas. It is scarce studies that deal with pregnancy and sexuality in the context of public health is a priority on continuing investigations in relation to these issues.
Keywords: Pregnancy; Sexuality; nursing